Pancreatic Heterotopia in the Small Bowel: A Case Report and Literature Review. Issue 6 (July 2022) - Chin, Ning-Hsuan; Wu, Jiann-Ming; Chen, Kuan-Chih; Lee, Tzong-Hsi; Lin, Cheng-Kuan; Chung, Chen-Shuan
Abstract: Diagnosing pancreatic heterotopia (PH) is challenging, because it is a rare congenital anomaly. We report the case of a 66-year-old man who presented with ileus and jejunal PH diagnosed using single-balloon enteroscopy. Reviewing 178 cases of small intestinal PH in the literature showed that (1) PH mostly occurred at the duodenum (61.8%), followed by the jejunum (22.5%) and ileum (14.6%); (2) patients with ileal PH were younger (mean, 40.7 vs 54.6 years; P < 0.001), while those with jejunal PH were older (mean, 59.5 vs 51.7 years; P = 0.006); (3) most patients with jejunal PH were females, while those with duodenal or ileal PH were predominantly males (M:F = 0.8:1 vs 2.5:1; P = 0.003); (4) asymptomatic cases were rare (15.2% vs 83.4% in small and nonsmall bowel, respectively); (5) most patients with ileal PH presented with bleeding (61.5%), while the remaining had abdominal pain (42.8%); (6) emergent operation was performed in 11 cases (6.2%), mainly at the jejunum (12.5%) and Meckel's diverticulum (25%); and (7) Heinrich's classification may be inconclusive. Enteroscopy was performed in only 6 cases (3.4%), and earlier diagnosis and further minimally invasive procedures could have been achieved with enteroscopy.